Composition of late summer diet by semi-domesticated reindeer in different grazing conditions in northernmost Finland - Bezard, Pauline; Brilland, Sophie; Kumpula, Jouko (Rangifer, 2015)
This study aims to investigate the diet composition of semi-domesticated reindeer (Rangifer tarandus tarandus) in late summer in different kinds of grazing conditions in northernmost Finland. The composition of diet by reindeer was determined on the grounds of microhistological analysis of feces samples collected in early August in different seasonal grazing areas (winter or summer/year-round grazing areas) in three reindeer management districts. Although the proportion of different plant groups varied between the studied districts, the quantified group of ground lichens (which also contained small amounts of mushrooms) was the most abundant, varying from 33.0 to 46.4% in the analyzed samples. In general, there were significant differences in the proportions of lichen between districts, but not between grazing areas. The proportion of lichen in samples increased significantly when the amount of lichen pasture around a sample site increased. The proportion of dwarf shrubs and leaves in samples varied from 24.9 to 37.9% and differed significantly between districts, but not between grazing areas. In the same way, the proportion of graminoids varied between 20.9 and 36.2% and differed significantly between districts and also between grazing areas. Higher amounts of graminoids in feces were observed in summer/year-round grazing areas than in winter grazing areas. Finally, the proportion of bryophytes varied between 2.9 and 6.5% and was significantly different between districts, but not between grazing areas. An increase in old and mature coniferous forest around a sample site significantly increased the amounts of bryophytes in samples. The results indicate that reindeer adapt their summer diet composition according to the availability of food plants. The results also show that when reindeer are allowed to select their summer ranges freely, reindeer tend to use lichen pastures intensively also during summer, which causes a considerable reduction in lichens due to grazing and trampling. Therefore, a proper seasonal pasture rotation system to protect lichen pastures from grazing and trampling, from early spring to late autumn, is an essential part of sustainable pasture use in reindeer herding.